THE INFLUENCE OF TOXIC DOSES OF OLIGOESTERS ON CARBOHYDRATE AND ENERGY METABOLISM OF LIVER OF WHITE RATS IN EXPERIMENT - Shcherban, N.G.; Zhukov, V.I.; Bezrodnaya, A.I.; Zaitseva, A.V.; Vashchuk, N.A.; Ovetchin, P.V.; Gopcalov, V.G. (World of Medicine and Biology, 2015)
The aim was to study the effect of long-term subtoxic influence of oligoesters on two brands of carbohydrate and energy metabolism of the liver in a subacute toxicological experiment on white rats. Xenobiotics L -3603-2-12 and L -10002-2-80 at a dose 110 і 1100 DL50 violate carbohydrate metabolism in the background of oppression bioenergetic processes. at a dose 1100 DL50 oligoesters stimulate the recovery of synthesis, which can be considered as voltage protective and adaptive mechanisms to ensure homeostatic functions. Oligoesters at long toxification 110 DL50 lead to the disruption of protective-adaptive mechanisms and the development of hypotoxical states that underlies the formation of dystrophic and destructive processes, the leading element of which is a membrane pathology.
Keywords: oligoesters; metabolism; toxicity; health